Evaluation of salivary ceruloplasmin for the diagnosis of Wilson’s disease - Nian Zhang; Limin Wu; Pengyu Jiang; Zhihui Ji; Miaozhu Yin; Huan Zhou; Lei He; Zehua Xia; Fengying Wang; Xin Xiao; Hui Han (Scientific Reports)
Abstract The serum ceruloplasmin assay is the most commonly used test for diagnosing Wilson’s disease (WD). Despite the utility of non-invasive tests for diagnosing WD, no such tests have been developed. Therefore, we aimed to identify a safe and non-invasive assay and determine the factors associated with salivary ceruloplasmin. The sample comprised 167 participants: 130 patients with WD (experimental group) and 37 individuals without WD (control group). Salivary ceruloplasmin’s diagnostic performance was assessed using a receiver operating characteristic curve analysis, and the diagnostic thresholds were determined. The Mann–Whitney U test for independent samples was used to compare intergroup variability between the control and WD groups. We used Pearson’s correlation coefficient to determine intergroup correlations between the blood and salivary ceruloplasmin levels of patients with WD. Salivary ceruloplasmin levels were significantly lower in the WD group than in the control group. Serum and salivary ceruloplasmin levels were positively correlated. The area under the curve for salivary ceruloplasmin was 0.9977. The critical value of salivary ceruloplasmin was 8.885 ng/mL, with a sensitivity of 99.23% and specificity of 100%. Evidently, salivary ceruloplasmin has substantial diagnostic value. Therefore, saliva analysis can be used as a non-invasive alternative to serum analysis for diagnosing WD.